IMPLEMENTATION OF SPECIALIZED NUTRITION WITH ALTERNATIVE PROTEIN SOURCES FOR ATHLETES IN HOTEL AND RESTAURANT INDUSTRY (Development Service Industry Management, 2025)
The article explores the prospects of introducing specialized nutrition programs for athletes within the hospitality industry, with a particular focus on the integration of alternative plant-based protein sources into the gastronomic offering of hotels and restaurants. Growing attention to wellness tourism and the global shift toward healthier, more sustainable diets highlight the urgent need for hotels to adapt their culinary strategies. Modern consumers, including both professional athletes and health-conscious guests, increasingly demand functional foods, gluten-free options, and vegan-friendly alternatives. Meeting these demands provides hotels with an opportunity to stand out in a highly competitive market while simultaneously strengthening their commitment to sustainability and customer well-being. A detailed analysis of the chemical composition and nutritional profile of hemp, flax, pumpkin seed proteins, quinoa, and spelt has been conducted. These products demonstrate a high concentration of essential amino acids, valuable fatty acids, fiber, vitamins, and minerals, which collectively contribute to balanced dietary support for individuals engaged in regular physical activity. Unlike many traditional protein sources, these alternatives also align with ecological and ethical principles, thus reinforcing the image of hotels as socially responsible enterprises. The study further presents examples of dishes tailored to hotel and restaurant settings that incorporate these proteins into diverse meal formats, from energizing breakfasts and light snacks to recovery-focused dinners. Such dishes not only ensure adequate protein intake but also offer guests novelty, gastronomic diversity, and a personalized experience aligned with their lifestyle. The inclusion of plant-based proteins in hotel menus expands the potential target audience by attracting athletes, wellness tourists, vegetarians, vegans, and environmentally aware travelers. The article concludes that the integration of plant-derived proteins into hotel gastronomy is a strategic step toward enhancing competitiveness, diversifying the customer base, and creating an innovative, client-oriented image. By adopting these nutritional practices, hotels can simultaneously address contemporary health trends, contribute to sustainable development, and offer guests added value that goes beyond traditional accommodation and dining services.
Keywords: nutrition; functional products; hotel and restaurant business